Effectiveness of Interval Training in Increasing Cardiorespiratory Endurance: A Systematic Review - Mochamad Ridwan; Erika Mahardini Zhuka; Aridhotul Haqiyah; Jaffry Zakaria (Physical Education Theory and Methodology)
Background. The rise in cardiovascular diseases has necessitated implementing effective interventions to improve cardiorespiratory endurance.